Rice straw derived cellulose acetate / g-C3N4 fiber membrane as well as preparation method and application thereof

Through electrospinning-electrospraying technology, g-C3N4 nanoparticles were anchored on cellulose acetate nanofibers to prepare rice straw-derived cellulose acetate/g-C3N4 fiber membranes, which solved the problems of nanoparticles agglomeration and difficulty in recycling, and improved photocatalytic performance and resource utilization efficiency.

CN119736761APending Publication Date: 2025-04-01WUHAN POLYTECHNIC UNIVERSITY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411618193.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

In the prior art, the preparation method of the supported fiber membrane leads to agglomeration of nanoparticles and difficulty in recycling, thereby reducing the photocatalytic effect.

Method used

Using electrospinning-electrospraying technology, g-C3N4 nanoparticles are uniformly anchored on cellulose acetate nanofibers to prepare rice straw-derived cellulose acetate/g-C3N4 fiber membranes.

Benefits of technology

The dispersion and photocatalytic properties of nanoparticles are improved, the degradation capacity of organic pollutants and pathogenic microorganisms in the water is enhanced, and the efficient utilization of rice straw resources and the reduction of environmental pollution is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736761A_ABST
    Figure CN119736761A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of crop straw recycling, and discloses a rice straw derived cellulose acetate / g-C3N4 fiber membrane and a preparation method and application thereof.The preparation method includes the steps that dichloromethane and acetic acid are evenly mixed to obtain a mixed solvent, rice straw derived cellulose acetate (CA) and polyvinylpyrrolidone (PVP) powder are added into the mixed solvent to be stirred, and a CA / PVP spinning solution is obtained; the preparation method comprises the following steps: calcining urea to obtain g-C3N4 nanosheets, and freezing and grinding the g-C3N4 nanosheets to obtain g-C3N4 nanoparticles; mixing the g-C3N4 nano particle powder with an absolute ethyl alcohol solution, performing ultrasonic treatment, and performing magnetic stirring to obtain a g-C3N4 electronic injection solution; according to the electrostatic spinning-electronic injection technology, a CA / PVP spinning solution and a g-C3N4 electronic injection solution are used for conducting electrostatic spinning and electrostatic spraying at the same time, an EE-CA / PVP / g-C3N4 fiber membrane is obtained, then the EE-CA / PVP / g-C3N4 fiber membrane is soaked in deionized water, freeze drying is conducted, and the rice straw derived cellulose acetate / g-C3N4 fiber membrane is obtained. The rice straw derived cellulose acetate / g-C3N4 fiber membrane has excellent photocatalytic performance and can be widely applied to the fields of degradation of pollutants in water and sterilization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of crop straw resource utilization, and in particular to a rice straw-derived cellulose acetate / g-C3N4 fiber membrane and a preparation method and application thereof. Background Art

[0002] Graphitic carbon nitride (g-C3N4) is a two-dimensional nanomaterial with a layered structure, which has excellent semiconducting properties, high thermal stability and chemical inertness. g-C3N4 can generate electron-hole pairs under light, promote charge separation, and participate in redox reactions. Therefore, g-C3N4 can be used as a multifunctional, environmentally friendly photocatalyst with excellent photocatalytic performance. It is widely used in treating organic pollutants in wastewater, degrading industrial dyes and heavy metals, etc. The preparation methods of g-C3N4 include thermal polymerization, solid-phase reaction, electrochemical deposition, and solvothermal method. Among them, the thermal polymerization method can prepare a layered g-C3N4 structure with a high specific surface area, and the method is easy to operate and has low cost, so it is widely used. However, the thermally polymerized g-C3N4 still has problems such as high recombination rate of photogenerated electrons and holes, easy agglomeration, and easy sedimentation.

[0003] There are abundant straw resources in my country's crops. Among them, rice straw is a kind of lignocellulosic biomass and also a renewable agricultural waste every year. Its main chemical components are cellulose, hemicellulose, lignin and ash. At present, the utilization efficiency of agricultural waste is not high, such as incineration, landfill composting and livestock feed. Cellulose in rice straw can be used as a raw material for the production of cellulose acetate (CA), which is another way to reduce environmental pollution. By loading the g-C3N4 structure on a fiber base to prepare nanofiber materials, not only can the dispersibility of g-C3N4 be improved, and the problems of easy agglomeration and difficult recycling of g-C3N4 can be solved, but also agricultural waste can be recycled and effectively utilized, reducing environmental pollution and realizing the efficient utilization of rice straw resources. In addition, the nanofiber material can also be used as a photocatalyst in the degradation of chemical pollutants.

[0004] In the prior art, the preparation of the loaded fiber membrane generally directly blends CA cellulose acetate with nanoparticles, and the particles are mainly located inside the fiber, and only when the added amount is very large will the particles be exposed outside the fiber to play a photocatalytic role. The internal particles cannot play a photocatalytic role, resulting in poor overall photocatalytic effect of the loaded fiber membrane. Therefore, the present application uses electrospinning-electrospray technology, that is, electrospinning and electrostatic spraying are performed simultaneously to anchor g-C3N4 on cellulose acetate (CA) nanofibers, solve the problems of agglomeration and difficulty in recycling of nanoparticles, efficiently degrade organic pollutants and pathogenic microorganisms in water, effectively alleviate energy shortages and solve environmental pollution problems, and at the same time realize the high-value utilization of rice straw resources. Summary of the invention

[0005] Based on the above, the purpose of the present invention is to provide a rice straw-derived cellulose acetate / g-C3N4 fiber membrane and a preparation method and application thereof, so as to prepare an environmentally friendly cellulose membrane catalyst with excellent photocatalytic performance, good recycling performance and easy recovery.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] A method for preparing a rice straw-derived cellulose acetate / g-C3N4 fiber membrane comprises the following steps:

[0008] Mixing dichloromethane and acetic acid uniformly to obtain a mixed solvent, adding rice straw-derived cellulose acetate and polyvinyl pyrrolidone powder into the mixed solvent and stirring to obtain a CA / PVP spinning solution;

[0009] The urea is heated in a muffle furnace to prepare g-C3N4 nanosheets, and the g-C3N4 nanosheets are placed in a cryogenic grinding machine, and the cryogenic grinding parameters are adjusted to grind the g-C3N4 nanoparticles;

[0010] The g-C3N4 nanoparticle powder is mixed with an anhydrous ethanol solution, subjected to ultrasonic treatment, and subjected to magnetic stirring to obtain a g-C3N4 electrospray solution;

[0011] EE-CA / PVP / g-C3N4 fiber membrane was prepared by electrospinning-electrospray technology, using CA / PVP spinning solution and g-C3N4 electrospray solution for simultaneous electrospinning and electrospinning, respectively, to evenly anchor g-C3N4 nanoparticles on the fiber surface to obtain EE-CA / PVP / g-C3N4 fiber membrane;

[0012] The EE-CA / PVP / g-C3N4 fiber membrane was immersed in deionized water to remove polyvinyl pyrrolidone, and then freeze-dried to obtain a rice straw-derived cellulose acetate / g-C3N4 fiber membrane.

[0013] As a preferred embodiment of the method for preparing a rice straw-derived cellulose acetate / g-C3N4 fiber membrane, the mass ratio of the rice straw-derived cellulose acetate and the polyvinyl pyrrolidone powder is (3-5):1; the volume ratio of the dichloromethane and the acetic acid is (1-3):1, and the concentration of the polyvinyl pyrrolidone powder in the mixed solvent is 0.025-0.05 g / mL.

[0014] As a preferred embodiment of the method for preparing a rice straw-derived cellulose acetate / g-C3N4 fiber membrane, the concentration of the g-C3N4 nanoparticle powder relative to the mixed solvent is 0.01 to 0.025 g / mL; in the g-C3N4 electrospray solution, the concentration of the g-C3N4 nanoparticle powder relative to the anhydrous ethanol is 0.003 to 0.01 g / mL.

[0015] As a preferred embodiment of the method for preparing rice straw-derived cellulose acetate / g-C3N4 fiber membrane, during the heating reaction in the muffle furnace, the temperature is increased to 500-550°C at a rate of 3-6°C / min and kept warm for 4-6 hours; the frozen grinding parameters include: grinding time of 30-90s and grinding frequency of 25-35Hz.

[0016] As a preferred solution for the preparation of rice straw-derived cellulose acetate / g-C3N4 fiber membrane, the electrospinning-electrospray technology device comprises an electrospinning machine, an electrostatic sprayer and a rotary drum collecting device, wherein the electrospinning machine is placed on one side of the rotary drum collecting device, and the electrostatic sprayer is placed on the other side of the rotary drum collecting device; when the electrospinning-electrospray technology is performed, the electrospinning machine and the electrostatic sprayer are used simultaneously to perform electrospinning and electrostatic spraying, respectively, and a rotary drum collecting device is used for collection, wherein the electrostatic sprayer is not connected to a high-voltage power supply when in use, and the electrospinning-electrospray technology allows the nanoparticles in the electrospray liquid to be evenly dispersed on the fiber surface.

[0017] As a preferred scheme for the preparation method of rice straw-derived cellulose acetate / g-C3N4 fiber membrane, the electrospinning process parameters include: spinning temperature of 23-27°C, humidity of 45-55%; spinning positive voltage of 8-12 kV, spinning negative voltage of -4--6 kV; feed rate of 0.3-0.5 ul / min; the distance between the spinneret and the drum collecting device is 10-20 cm.

[0018] As a preferred embodiment of a method for preparing a rice straw-derived cellulose acetate / g-C3N4 fiber membrane, the method for preparing the rice straw-derived cellulose acetate comprises:

[0019] The rice straw is washed, dried, crushed and sieved to obtain rice straw powder, the rice straw powder is pretreated with an ethanol solution in a high temperature reactor, and then subjected to an alkali treatment and H2O2 bleaching to obtain rice straw-derived cellulose;

[0020] Acetic anhydride and glacial acetic acid are added to the rice straw-derived cellulose to prepare rice straw-derived cellulose acetate through acetylation reaction.

[0021] As a preferred embodiment of the method for preparing a rice straw-derived cellulose acetate / g-C3N4 fiber membrane, the rice straw particle size is 50 to 100 meshes;

[0022] During the pretreatment process, the mass concentration of the ethanol solution is 60-70wt%, the heating reaction temperature is 160-240°C, and the reaction time is 2-3h;

[0023] During the alkali treatment and H2O2 bleaching process, 4-6 wt% alkali solution is used to stir and react at 85-95°C for 1.5-2.5 hours, and after the reaction is completed, it is filtered, and then heated and stirred with 2 wt% H2O2 solution at 65-75°C for 1.5-2.5 hours to obtain rice straw-derived cellulose;

[0024] During the acetylation reaction, the mass ratio of the rice straw-derived cellulose to the acetic anhydride is 1:(3-5), and the concentration range of the rice straw-derived cellulose in the glacial acetic acid is 0.05-0.07 g / mL.

[0025] A rice straw-derived cellulose acetate / g-C3N4 fiber membrane is prepared by any of the preparation methods described above.

[0026] The invention discloses an application of a rice straw-derived cellulose acetate / g-C3N4 fiber membrane. The rice straw-derived cellulose acetate / g-C3N4 fiber membrane is used as a photocatalyst in water pollution treatment and photocatalytic sterilization.

[0027] The beneficial effects of the present invention are:

[0028] The present invention provides a rice straw-derived cellulose acetate / g-C3N4 / TiO2 fiber membrane and a preparation method and application thereof. Block g-C3N4 (CN) is synthesized by high temperature pyrolysis, and then a powdered CG-CN catalyst is obtained by freeze grinding. The powdered CG-CN catalyst is loaded onto nanofibers by electrospinning-electrospray technology to prepare EE-CA / CGCN fiber membranes. Compared with the traditional electrospinning method, the g-C3N4 particles of the EE-CA / CGCN fiber membranes are more exposed on the surface of the nanofibers, providing more active sites, which is beneficial to improving the photocatalytic performance. The CG-CN of the EE-CA / CGCN fiber membrane is evenly dispersed on the fiber surface, which inhibits the agglomeration of nanoparticles to a certain extent and improves the stability of the membrane catalytic material. In addition, the present application uses an electrostatic sprayer for electrostatic spraying, which does not need to be connected to a high-voltage power supply when used, is easy to use, and reduces process costs.

[0029] When the loading amount of CG-CN is 0.10 g, EE-CA / CGCN (0.10) It exhibits better adsorption and photocatalytic performance, with the degradation rate of MB reaching over 98.54% after 30 minutes of illumination, and the degradation rate of TC reaching over 94.34% after 60 minutes of illumination. It has excellent degradation performance for MB and TC and can efficiently degrade pollutants.

[0030] When irradiated with λ>420nm light for 60min, EE-CA / CGCN (0.10) It exhibits good antibacterial properties against Escherichia coli, with an antibacterial rate of more than 90.12%, so it can be widely used in the fields of degrading pollutants in water and antibacterial. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments of the present invention. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the contents of the embodiments of the present invention and these drawings without paying any creative work.

[0032] Figure 1 SEM and HR-TEM images, where (ab)EE-CA / CGCN (0.05) SEM images; (cd) EE-CA / CGCN (0.10) SEM images; (ef) EE-CA / CGCN (0.15) SEM image; (gh) E-CA / CGCN (0.10) SEM images; (ij) EE-CA / CGCN (0.10) HR-TEM images of

[0033] Figure 2 CN, CGCN, E-CA / CGCN (0.10) and XRD spectra of EE-CA / CGCN fiber membranes with different CGCN contents;

[0034] Figure 3 CA, CGCN, E-CA / CGCN (0.10) and FT-IR spectra of EE-CA / CGCN fiber membranes with different CGCN contents;

[0035] Figure 4 Is EE-CA / CGCN (0.10) EDS and Mapping images of fiber membranes, where (a) EE-CA / CGCN (0.10) EDS image of fiber membrane; (b) EE-CA / CGCN (0.10) Mapping diagram of (c) C element; (d) N element; (e) O element

[0036] Figure 5 CN, CGCN, E-CA / CGCN (0.10) and EE-CA / CGCN (0.10)N2 adsorption-desorption isotherms and pore size distribution of fiber membrane;

[0037] Figure 6 is the UV-visible diffuse reflectance spectrum and energy band curve diagram, where (a) EE-CA / CGCN and E-CA / CGCN (0.10) UV-visible diffuse reflectance spectrum of fiber membrane; (b) EE-CA / CGCN (0.10) and E-CA / CGCN (0.10) Energy band diagram of fiber membrane;

[0038] Figure 7 Yes CN, CGCN, EE-CA / CGCN and E-CA / CGCN (0.10) Fluorescence spectrum of fiber membrane;

[0039] Figure 8 It curve and EIS spectrum, where (a) EE-CA / CGCN (0.10) and E-CA / CGCN (0.10) it curve of fiber membrane; (b) EIS spectrum;

[0040] Fig. 9 CA, EE-CA / CGCN (0.10) and E-CA / CGCN (0.10) The test results of the contact angle of the fiber membrane to water;

[0041] Fig.10 is the photocatalytic degradation efficiency and the corresponding pseudo-first-order rate constant, where (ab) the photocatalytic degradation efficiency of methylene blue and the corresponding pseudo-first-order rate constant; (cd) the photocatalytic degradation efficiency of tetracycline and the corresponding pseudo-first-order rate constant; (ef) EE-CA / CGCN (0.10) Degradation efficiency of fiber membranes for different dyes and the corresponding pseudo-first-order rate constants;

[0042] Fig.11 Is EE-CA / CGCN (0.10) Repeated test diagram of the fiber membrane's photocatalytic degradation of methylene blue;

[0043] Fig.12 Is EE-CA / CGCN (0.10) Time-varying diagram of the 3D fluorescence spectrum of the fiber membrane, where (ac) methylene blue; (df) rhodamine B; (gi) methyl orange;

[0044] Fig.13 Is EE-CA / CGCN (0.10) Degradation efficiency of methylene blue by fiber membrane under the action of different quenchers (a) and the corresponding pseudo-first-order rate (b);

[0045] Fig.14 The antibacterial effect image, bacterial survival rate curve and bacterial removal efficiency bar graph are shown in Figure 1, where (ad) blank test; (eh) EE-CA / CGCN(0.10) Dark's antibacterial effect image; (il)EE-CA / CGCN (0.10) Light on antibacterial effect image; (m) bacterial survival rate curve; (n) bacterial removal efficiency bar graph of the sample under visible light (λ>420nm) irradiation. DETAILED DESCRIPTION

[0046] For ease of understanding of the present invention, the present invention will be described more fully below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive. Unless otherwise defined, all technical and scientific terms used in the present invention belong to the technical field of the present invention.

[0047] This embodiment provides a method for preparing a rice straw-derived cellulose acetate / g-C3N4 fiber membrane, which specifically includes:

[0048] S100, mixing dichloromethane and acetic acid uniformly to obtain a mixed solvent, adding rice straw-derived cellulose acetate and polyvinyl pyrrolidone powder into the mixed solvent and stirring to obtain a CA / PVP spinning solution;

[0049] Specifically, the mass ratio of rice straw-derived cellulose acetate and polyvinyl pyrrolidone powder is (3-5):1; the volume ratio of dichloromethane and acetic acid is (1-3):1, and the concentration of polyvinyl pyrrolidone powder in the mixed solvent is 0.025-0.05 g / ml.

[0050] S200, heating urea in a muffle furnace to prepare g-C3N4 nanosheets, placing the g-C3N4 nanosheets in a freeze grinder, adjusting freeze grinding parameters, and grinding to obtain g-C3N4 nanoparticles;

[0051] Specifically, during the heating reaction in the muffle furnace, the temperature is raised to 500-550° C. at a rate of 3-6° C. / min and kept warm for 4-6 hours; the freezing grinding parameters include: the grinding time is 30-90 s and the grinding frequency is 25-35 Hz.

[0052] S300, mixing the g-C3N4 nanoparticle powder with an anhydrous ethanol solution, ultrasonically treating, and magnetically stirring to obtain a g-C3N4 electrospray solution;

[0053] Specifically, the concentration of g-C3N4 nanoparticle powder relative to the mixed solvent is 0.01-0.025 g / mL, and the concentration of g-C3N4 nanoparticle powder relative to anhydrous ethanol is 0.003-0.01 g / mL. Exemplarily, 0.8 g of rice straw-derived cellulose acetate, 0.2 g of polyvinyl pyrrolidone powder, and a mixed solution including 2 ml of acetic acid and 4 ml of dichloromethane are used. At this time, 0.05-0.15 g of g-C3N4 nanoparticle powder is reacted with 15 ml of anhydrous ethanol solution to prepare a g-C3N4 electrospray solution for electrospray loading, preferably 0.10 g of g-C3N4 nanoparticle powder is reacted with 15 ml of anhydrous ethanol solution.

[0054] S400, EE-CA / PVP / TiO2 fiber membrane was prepared by electrospinning-electrospray technology, CA / PVP spinning solution and TiO2 electrospray solution were used for electrospinning and electrospinning respectively, TiO2 nanoparticles were evenly anchored on the fiber surface, and EE-CA / PVP / TiO2 fiber membrane was obtained.

[0055] Specifically, g-C3N4 nanoparticles are loaded on cellulose acetate nanofibers using electrospinning-electrospraying technology. Pure cellulose acetate fibers are obtained by electrospinning while g-C3N4 nanoparticles are electrosprayed. While the fibers are solidified, the g-C3N4 nanoparticles are directly exposed on the fiber surface. There are no nanoparticles inside the fibers, exposing more active sites, hindering the recombination of free carriers, and improving the separation efficiency of photogenerated carriers and the interfacial charge transfer efficiency, thereby improving the catalytic activity and chemical stability of the material.

[0056] Specifically, the device of electrostatic spinning-electrospray technology includes an electrostatic spinning machine, an electrostatic sprayer and a rotary drum collection device, the electrostatic spinning machine is placed on one side of the rotary drum collection device, and the electrostatic sprayer is placed on the other side of the rotary drum collection device; when performing electrostatic spinning-electrospray technology, the electrostatic spinning machine and the electrostatic sprayer are used simultaneously to perform electrostatic spinning and electrostatic spraying respectively, and the rotary drum collection device is used for collection. Preferably, the positions of the electrostatic spinning machine, the electrostatic sprayer and the rotary drum collection device can be in a straight line. Of course, in other embodiments, the positions of the electrostatic spinning machine, the electrostatic sprayer and the rotary drum collection device can also be placed at an angle, and the spray generated by the electrostatic sprayer can be loaded onto the fiber filaments collected by the collection device. In addition, an electrostatic sprayer is used for electrostatic spraying. The electrostatic sprayer does not need to be connected to a high-voltage power supply when used, is easy to use, and reduces process costs. In this embodiment, it is preferably a handheld electrosprayer, which is convenient to operate and reduces process costs. Of course, in other embodiments, a fixed electrosprayer can also be used to meet the load.

[0057] More specifically, the process parameters of electrospinning include: spinning temperature of 23-27°C, humidity of 45-55%; spinning positive voltage of 8-12kV, spinning negative voltage of -4--6kV; feed rate of 0.3-0.5ul / min; the distance between the spinneret and the drum collection device is 10-20cm.

[0058] S500. Soak the EE-CA / PVP / g-C3N4 fiber membrane in deionized water to remove polyvinyl pyrrolidone, and freeze-dry it to obtain a rice straw-derived cellulose acetate / g-C3N4 fiber membrane, which is recorded as EE-CA / CG-CN fiber membrane.

[0059] Specifically, the preparation method of rice straw-derived cellulose acetate includes:

[0060] S001, washing, drying, crushing and sieving the rice straw to obtain rice straw powder, pre-treating the rice straw powder with an ethanol solution in a high-temperature reactor, and then performing an alkali treatment and H2O2 bleaching to obtain rice straw-derived cellulose;

[0061] The rice straw particle size is 50-100 mesh;

[0062] During the pretreatment process, the mass concentration of the ethanol solution is 60-70wt%, the heating reaction temperature is 160-240°C, and the reaction time is 2-3h;

[0063] During the alkali treatment and H2O2 bleaching process, 4-6 wt% alkali solution is stirred at 85-95°C for 1.5-2.5 hours, filtered after the reaction is completed, and then heated and stirred at 65-75°C for 1.5-2.5 hours with 2 wt% H2O2 solution to obtain rice straw-derived cellulose;

[0064] S002, adding acetic anhydride and glacial acetic acid to rice straw-derived cellulose to prepare rice straw-derived cellulose acetate through acetylation reaction;

[0065] The mass ratio of rice straw-derived cellulose to acetic anhydride is 1:(3-5), and the concentration range of rice straw-derived cellulose in glacial acetic acid is 0.05-0.07 g / mL. In a specific embodiment, 7-9 mL of glacial acetic acid is added to every 0.5 g of rice straw cellulose for reaction.

[0066] The present invention will be further described below by means of specific examples.

[0067] Example 1

[0068] The rice straw is washed, dried, crushed and sieved to obtain rice straw powder, and the rice straw powder is pretreated with an ethanol solution in a high-temperature reactor at 200° C. for 3 h, and then subjected to alkali treatment and H2O2 bleaching to obtain rice straw-derived cellulose; 2 g of acetic anhydride and 8 ml of glacial acetic acid are added to 0.5 g of rice straw-derived cellulose to obtain rice straw-derived cellulose acetate through an acetylation reaction; of course, in other embodiments, 1.5 g of acetic anhydride and 7 ml of glacial acetic acid are added to 0.5 g of rice straw-derived cellulose, or 2.5 g of acetic anhydride and 9 ml of glacial acetic acid are added to 0.5 g of rice straw-derived cellulose to obtain rice straw-derived cellulose acetate through an acetylation reaction, which is determined according to actual conditions.

[0069] 4 ml of dichloromethane and 2 ml of acetic acid were evenly mixed to obtain a mixed solvent, 0.8 g of rice straw-derived cellulose acetate and 0.2 g of polyvinyl pyrrolidone powder were added to the mixed solvent, and stirred for 6 hours using a magnetic stirrer to obtain a CA / PVP spinning solution; at this time, the mass ratio of rice straw-derived cellulose acetate and polyvinyl pyrrolidone powder was 4:1; the volume ratio of dichloromethane and acetic acid was 2:1, and the concentration of polyvinyl pyrrolidone powder in the mixed solvent was 0.033 g / mL. Of course, in other embodiments, the mass ratio of rice straw-derived cellulose acetate and polyvinyl pyrrolidone powder was 3:1 or 5:1; the volume ratio of dichloromethane and acetic acid was 3:1 or 1:1, and the concentration of polyvinyl pyrrolidone powder in the mixed solvent was 0.025 g / mL or 0.05 g / mL, which was determined according to actual conditions.

[0070] 20 g of urea was loaded into a porcelain boat, which was placed in a muffle furnace, and the temperature was raised to 520 °C at a rate of 5 °C / min, and kept warm for 4 hours. After the muffle furnace was naturally cooled to room temperature, the obtained product was ground and collected to obtain g-C3N4 nanosheets (CN);

[0071] 1 g of the CN prepared above was placed in a 50 mL grinding jar, and then stainless steel grinding balls were added. The jar cover was tightened and placed in a cryogenic grinder. After the cryogenic grinder was cooled to -50 °C, the cryogenic grinding parameters (grinding time 60 s, grinding frequency 30 Hz) were adjusted for grinding, and finally g-C3N4 nanoparticles (CGCN) were obtained;

[0072] 0.1 g of CGCN solid powder was mixed with 15 mL of anhydrous ethanol solution, ultrasonically treated for 90 min, and magnetically stirred for 1 h to make CGCN uniformly dispersed in the ethanol system to obtain a g-C3N4 electrospray solution.

[0073] The electrospinning machine is placed on one side of the drum collecting device, and the electrostatic sprayer is placed on the other side of the drum collecting device. Electrospinning and electrostatic spraying are performed simultaneously. The CA / PVP spinning solution is transferred to a syringe to prepare for electrospinning. When the electrospinning machine starts working, the CA / PVP nanofibers are collected by the drum collecting device, and a handheld electrosprayer filled with g-C3N4 electrospray solution is used to work at the same time, spraying for 6-8s at a certain interval until the spinning is completed to obtain the EE-CA / PVP / CGCN fiber membrane. Among them, the electrospinning process parameters are as follows: the spinning temperature and humidity are 25°C and 50% respectively; the spinning positive and negative voltages are 10kV and -5kV respectively; the feed rate is 0.4ul / min; the distance between the spinneret and the drum collecting device is 15cm.

[0074] The EE-CA / PVP / CG-CN fiber membrane was immersed in deionized water for 24 h to remove the polyvinyl pyrrolidone and freeze-dried to obtain the rice straw-derived cellulose acetate / g-C3N4 fiber membrane, which was denoted as EE-CA / CGCN (0.10) Fiber membrane.

[0075] Example 2

[0076] The preparation process was basically the same as that in Example 1, wherein 0.05 g of g-C3N4 powder was mixed with 15 mL of C2H5OH to obtain a rice straw-derived cellulose acetate / g-C3N4 fiber membrane, denoted as EE-CA / CGCN (0.05) Fiber membrane.

[0077] Example 3

[0078] The preparation process was basically the same as that in Example 1, wherein 0.15 g of g-C3N4 powder was mixed with 15 mL of C2H5OH to obtain a rice straw-derived cellulose acetate / g-C3N4 fiber membrane, denoted as EE-CA / CGCN (0.15) Fiber membrane.

[0079] In order to further illustrate the key points of this patent, a comparative case is added for illustration.

[0080] Comparative Example 1

[0081] The CG-CN powder was prepared by the same method as in Example 1, and the CA / PVP spinning solution was prepared by the same method as in Example 1. 0.10 g of CG-CN powder was weighed and placed in the CA / PVP spinning solution, and magnetic stirring was performed for 6 h to obtain the CA / PVP / CGCN spinning solution.

[0082] The uniformly stirred CA / PVP / CGCN spinning solution was electrospun, and the spinning parameters were as follows: spinning temperature 25°C, humidity 40%, spinning positive voltage 20kV, negative voltage 10kV, injection rate 1.50ul / min, and the distance between the needle and the collection device was 15cm;

[0083] Finally, E-CA / PVP / CGCN was prepared by the above electrospinning technology. (0.10) The fiber membrane was immersed in deionized water for 24 h to remove PVP, and then freeze-dried to obtain E-CA / CGCN (0.10) Fiber membrane.

[0084] Comparative Example 2

[0085] The same rice straw-derived acetate fiber (CA) as in Example 1 was prepared, and CA was directly electrospun to obtain a pure CA fiber membrane.

[0086] The photocatalytic performance of the fiber membranes prepared in Examples 1-3 and Comparative Examples 1-2 was analyzed and relevant photocatalytic tests were performed.

[0087] 1. Photocatalytic test

[0088] (1) Photocatalytic degradation test

[0089] Different organic dyes, rhodamine B (RhB), methylene blue (MB) and methyl orange (MO), were used as simulated organic pollutants to evaluate the photocatalytic activity of EE-CA / CG-CN under visible light irradiation, and all tests were repeated 3 times. First, 50 mg of film photocatalyst was added to 50 mL of organic dye aqueous solution (10 mg / L). The above photocatalyst suspension was stirred in the dark for 30 minutes under magnetic stirring. After reaching adsorption-desorption equilibrium, xenon lamp irradiation was used as simulated sunlight irradiation, and the circulating condensed water was set to 20 ° C. 5 mL of equal amount was sampled every 5 minutes, and the resulting solution was filtered through a 0.22 μm filter membrane. The concentrations of RhB, MB and MO solutions were measured at 554 nm, 664 nm and 465 nm respectively using a UV-visible spectrophotometer.

[0090] (2) Photocatalytic cycle test

[0091] In order to verify the stability of the EE-CA / CG-CN fiber membrane, the membrane catalyst was subjected to 5 cycles of testing under the same photocatalytic conditions as mentioned above: after the photocatalytic test, the EE-CA / CG-CN fiber membrane was collected and repeatedly washed with anhydrous ethanol and deionized water to make the catalyst surface colorless, and then dried and then subjected to cycle testing. This process was repeated 5 times.

[0092] (3) Photocatalytic antibacterial test

[0093] The photocatalytic antibacterial activity of EE-CA / CG-CN fiber membrane against Escherichia coli was detected by plate colony counting method, and all tests were carried out in parallel 3 times. The nutrient source of bacteria was LB (1g beef extract, 1g NaCl, 2g peptone, 4g agar powder, 200mL H2O), and all glassware was sterilized at 121℃ for 30min before testing. The photocatalytic antibacterial test process is described as follows: First, 50mg of EE-CA / CG-CN (0.10) The fiber membrane is placed in a beaker and diluted with 0.9% NaCl solution. Secondly, the bacteria are taken out of the culture solution and added to the beaker containing the sample so that the bacteria and the sample are fully mixed and in contact in a dark environment. Third, a xenon lamp (λ>420nm) is used as a light source for vertical downward irradiation, and constant stirring is maintained throughout the test. At fixed time intervals, 1mL of the mixture is transferred with a pipette and diluted to an appropriate concentration. Finally, 0.1ml of the bacterial solution is evenly applied to the culture medium using the plate coating method. It is then placed in a constant temperature incubator and cultured overnight at 37°C. The number of colonies on each plate is counted using a colony counter to calculate the photocatalytic inhibition rate of the sample.

[0094] 2. Related characterization and performance analysis

[0095] (1) Morphology and structure characterization

[0096] The surface morphology of CA / CGCN fiber membrane was characterized by SEM. Figure 1 (af) It can be seen that in the EE-CA / CGCN fiber membrane prepared by electrospinning-electrospraying, CG-CN is loaded on the surface of the nanofibers, and with the increase of CG-CN loading, the CG-CN nanosheets loaded on the surface of CA / CGCN nanofibers gradually increase until the entire fiber is covered. When the CG-CN loading reaches 0.15g, the CG-CN nanosheets agglomerate, which is not conducive to the exposure of the active sites on the catalyst surface. Figure 1 (gh) is E-CA / CGCN prepared by electrospinning (0.10) From the SEM image of the fiber membrane, it can be observed that the CG-CN nanosheets are wrapped inside the fiber, and the fiber presents an uneven bone-like structure. Therefore, the CA / CGCN fiber membranes prepared by the two methods have completely different states of CG-CN nanosheets loaded on the fiber, one is anchored on the surface of the nanofiber, and the other is wrapped in the fiber. The microstructure of the sample was further analyzed by TEM, such as Figure 1 (ij) shows EE-CA / CGCN (0.10) TEM image of the fiber membrane. It can be seen from the figure that the CG-CN nanosheets are tightly combined with the fibers to form a close interface contact, and the CG-CN nanosheets are evenly dispersed on the fiber surface, which is beneficial to the EE-CA / CGCN(0.10) The exposure of active sites on the fiber membrane surface promotes the photocatalytic reaction.

[0097] (2) X-ray diffraction (XRD) characterization

[0098] Figure 2 CN, CGCN, E-CA / CGCN (0.10) XRD spectra of EE-CA / CGCN fiber membranes with different CGCN contents. As can be seen from the figure, the CN nanosheets show two diffraction peaks at 13.17° and 27.40°, which can be attributed to the (100) crystal plane and (002) crystal plane of graphite-like carbon nitride, which indicates that phase-pure CN nanosheets were synthesized by this test method. By comparing CN nanosheets and CGCN nanoparticles, it was found that the two characteristic peaks of the two are roughly the same, but the strength is different. This shows that the CGCN and CN obtained by cryogenic grinding are still graphite-like phase crystal structures and there are no other impurities. For composite materials, all materials have diffraction peaks at 2θ=27.54°, and as the CGCN content increases, the peak at this location gradually increases. This shows that the more CGCN content, the more CGCN loaded on the EE-CA / CGCN membrane begins to agglomerate, resulting in a decrease in the interlayer spacing between CGCN particles. Compared with the E-CA / CGCN prepared by electrostatic co-spinning (0.10) , and found that its characteristic peak intensity was relatively weak, which may be due to the encapsulation of CGCN inside the fiber by electrostatic blending, which is consistent with the above SEM results.

[0099] (3) Fourier transform infrared spectroscopy (FT-IR) characterization

[0100] Using infrared spectroscopy to characterize CA, CGCN, and E-CA / CGCN (0.10) The chemical structures of EE-CA / CGCN fiber membranes with different CGCN contents were characterized. Figure 3 As shown in (a), the CA membrane has a wavelength of 3446 cm -1 and 2956cm -1 The peaks at 1752 cm -1 (C=O stretching vibration), 1375cm -1 (CH bending vibration in acetoxy group) and 1236 cm -1 There are three peaks at 1047 cm-1 (-CO- stretching vibration in acetoxy group), which correspond to the three important ester bonds in CA molecule. -1 The peak at 3000 to 3500 cm-1 is attributed to the vibration of the COC pyran ring skeleton in the CA molecule. -1The characteristic peaks between 1240 and 1630 cm represent the stretching vibrations of NH and OH. -1 A series of peaks at 810 cm-1 correspond to the stretching vibration of the CN heterocyclic structure. -1 The absorption peak at corresponds to the bending vibration of the triazine ring structure. Figure 3 In (b), we can see a series of EE-CA / CGCN and E-CA / CGCN (0.10) The Fourier transform infrared spectrum of the fiber membrane contains the characteristic peaks of CA (1047, 1236, 1375 and 1752 cm -1 ) and the characteristic peaks of CGCN (810 cm -1 1200~1600cm -1 Multiple peaks and 3000~3500cm -1 The broad absorption peak of EE-CA / CGCN and E-CA / CGCN with different CGCN contents (0.10) The fiber membrane was successfully synthesized, and CGCN particles were successfully loaded onto CA fibers.

[0101] (4) X-ray energy spectrum (EDS) and element distribution map (Mapping)

[0102] In order to study EE-CA / CGCN (0.10) The chemical composition, element content and distribution of the fiber membrane were studied by EDS and Mapping (such as Figure 4 As shown in Figure 2 ). Since CA contains only C, H and O, while CGCN contains C and N, EDS analysis confirmed that C, N and O are the main components of EE-CA / CGCN. (0.10) Expected elements of the complex. Figure 4 EE-CA / CGCN is also listed in (a) (0.10) EDS studies show that the prepared EE-CA / CGCN (0.10) The composite material is pure and not contaminated by other elements. Figure 4 (be) It can be clearly seen that EE-CA / CGCN (0.10) The C, N, and O elements are evenly distributed on the composite fibers, which is consistent with the EDS results.

[0103] (5) Characterization of specific surface area and pore size distribution

[0104] A specific surface area analyzer was used to perform nitrogen adsorption-desorption tests on the material to detect the specific surface area, pore volume and pore size distribution of the material. N2 was used as the protective gas during degassing and the temperature was set to 90°C.

[0105] The specific surface area and pore size distribution were determined by N2 adsorption-desorption isotherms of the selected samples, as shown in Table 1. Figure 5 As can be seen in Figure 2, all the studied photocatalysts exhibit type IV(a) isotherms with H3 hysteresis loops, indicating a mesoporous structure with slit-like pores. Cryo-grinding enables us to obtain high surface area CGCN based on CN by simple mechanochemistry, that is, rapid grinding in a cryo-grinding machine at low temperatures. Compared with CN solid (33.95 m 2 / g), the specific surface area of ​​CGCN increased significantly, reaching 47.15 m 2 / g. In the fiber membrane prepared by loading CGCN on CA fiber with CA as carrier, the specific surface area difference of fiber membrane prepared by different processes was compared. Among them, EE-CA / CGCN prepared by electrospinning-electrospray (0.10) Fiber membrane (12.09m 2 / g) is slightly higher than that of E-CA / CGCN prepared by electrospinning. (0.10) Fiber membrane (11.51m 2 / g), which may be due to the different loading methods of CGCN. (0.10) The CGCN of E-CA / CGCN was more exposed on the fiber surface, while (0.10) More are embedded in the fiber, which is consistent with the above SEM results. The average pore radius and total pore volume of the two are almost the same, but their pore volumes are much higher than those of CN and CGCN solid powders.

[0106] Table 1 Specific surface area and pore structure parameters of materials

[0107]

[0108] (6) UV-Visible absorption spectroscopy (DRS) characterization

[0109] The optical properties of photocatalysts such as Figure 6 As shown in Figure 2, it can be observed that with the addition of CGCN, the absorption band edge of the catalyst first increases and then decreases, and the absorption band edge of the EE-CA / CGCN fiber membrane is greater than that of the E-CA / CGCN (0.10) This indicates that the band gap of the membrane material (EE-CA / CGCN) prepared by electrospinning-electrospraying method is smaller than that of the electrospinning method (E-CA / CGCN). The band gap energy of the material can be calculated by the Kubelka-Munk function

[0110] (αhv) n =A(hv-Eg)

[0111] Where: α represents the absorption coefficient, hν is the photon energy, A is a constant, Eg is the band gap energy value, and n is 2. 2 Plotting hν, such as Figure 6 As shown in (b), EE-CA / CGCN (0.10) With E-CA / CGCN (0.10) The band gaps are 2.75eV and 4.90eV respectively.

[0112] (7) Three-dimensional fluorescence (3DEEM) characterization

[0113] Figure 7 CN, CGCN powder, EE-CA / CGCN and E-CA / CGCN (0.10) Fluorescence spectrum of the fiber membrane. Usually, the intensity of the emission spectrum of the fluorescence spectrophotometer (PL) excited by ultraviolet light can reflect the recombination rate of photogenerated electron-hole pairs. The stronger the spectrum intensity, the higher the free carrier recombination rate, and vice versa. As can be seen from the figure, the CN solid powder has a strong photoluminescence emission peak near 455nm. Compared with powdered CN, the fluorescence intensity of CGCN powder after freeze-grinding treatment is lower, corresponding to a lower photogenerated carrier recombination rate. With the increase of CGCN content, the fluorescence intensity first decreases and then increases, indicating that when the content of added CGCN is 0.10g, CGCN is more evenly distributed in the fiber membrane. And from the figure, we can see that E-CA / CGCN (0.10) The fluorescence signal of the fiber membrane is the strongest, which indicates that the fiber membrane obtained by using CA as the base membrane and anchoring CGCN powder on the fiber surface by synchronous electrospraying hinders the recombination of photogenerated electron-hole pairs; on the contrary, E-CA / CGCN obtained by electrostatic blending (0.10) The CGCN in the fiber film re-aggregated, and the recombination rate of photogenerated electron-hole pairs increased. (0.10) The fiber membrane has the strongest photocatalytic ability.

[0114] 3. Other performance analysis

[0115] (1) Photoelectrochemical performance test

[0116] Good separation efficiency of photogenerated carriers can bring about good photocatalytic activity. Therefore, we used electrochemical methods such as transient photocurrent (TPC) and electrochemical impedance spectroscopy (EIS) to test the separation and transfer efficiency of photogenerated holes and electrons in the samples. Figure 8 (a) Depicts EE-CA / CGCN (0.10) and E-CA / CGCN (0.10)Photocurrent curve of fiber membrane under visible light irradiation. The appearance of current means the separation of electron-hole pairs under light irradiation, while the decay of current is due to the recombination of photogenerated carriers. Figure 8 (a) It can be seen that EE-CA / CGCN (0.10) The photocurrent intensity is significantly higher than that of E-CA / CGCN (0.10) , indicating EE-CA / CGCN (0.10) The fiber membrane has a higher photogenerated electron-hole separation efficiency and faster interfacial charge transfer. In addition, in order to explore the photogenerated electron transfer efficiency of the catalyst, the electrochemical impedance spectroscopy (EIS) test was performed on the catalyst. Figure 8 (b) shows the EE-CA / CGCN (0.10) and E-CA / CGCN (0.10) EIS spectrum curve of fiber membrane. EE-CA / CGCN (0.10) With the smallest Nyquist semicircle radius, a smaller arc radius reflects a higher carrier transfer efficiency, which is consistent with the photocurrent curve Figure 1 This shows that EE-CA / CGCN (0.10) It exhibits higher charge transfer efficiency, thus greatly improving the photocatalytic degradation performance.

[0117] (2) Optical contact angle test

[0118] Measurement of CA, EE-CA / CGCN by contact angle (0.10) and E-CA / CGCN (0.10) The surface hydrophilicity of the membrane is shown in the following table. Fig. 9 As shown. It can be seen that compared with the CA film, EE-CA / CGCN (0.10) and E-CA / CGCN (0.10) The fiber membrane showed a smaller contact angle and was hydrophilic. This may be due to the loading of g-C3N4 on the CA nanofibers and the presence of OH in the polymerization solution. - The hydrogen bonds established between the triazine units lead to a reduction in the surface roughness of the membrane. (0.10) Compared with the fiber membrane, EE-CA / CGCN prepared by electrospinning-electrospray (0.10) It shows better hydrophilic properties. This may be related to the state of g-C3N4 loaded on the fiber. The hydrophilic g-C3N4 nanoparticles are loaded on EE-CA / CGCN (0.10) The fiber membrane surface causes the formation of hydrogen bonds with water molecules, thus forming a stronger affinity between water and the membrane surface, resulting in a decrease in the water contact angle.

[0119] (3) Photocatalytic performance

[0120] MB and TC were used as target pollutants, and the photocatalytic activity of CA / CN fiber membrane was evaluated by the performance of photocatalytic degradation of pollutants. Fig.10 (a) The degradation efficiency of MB dye by four different CA / CN fiber membranes was compared. As can be seen from the figure, MB was degraded for materials with different CG-CN contents, and the degradation efficiency was different. With the increase of the amount of CG-CN added, the photocatalytic degradation efficiency of MB first increased and then decreased after 30 minutes of illumination, which shows that adding an appropriate amount of CG-CN powder can effectively improve the photocatalytic activity of the fiber membrane. In addition, the difference in MB degradation efficiency of CA / CN fiber membranes prepared by different methods under the condition of the same CG-CN addition amount was compared. E-CA / CGCN prepared by electrostatic co-spinning method (0.10) Compared with the fiber membrane (84.32%), the EE-CA / CGCN prepared by electrospinning-electrospray (0.10) The degradation rate of MB by the fiber membrane was further improved, reaching 94.97% after 20 min of light exposure. (0.10) The fiber membrane is an efficient catalyst for MB degradation. At the same time, all degradation curves conform to pseudo-first-order kinetics. Fig.10 (b) EE-CA / CGCN can be clearly seen (0.10) The rate constant of the fiber membrane is the largest, reaching 0.1341min -1 , respectively EE-CA / CG-CN (0.05) EE-CA / CG-CN (0.15) and E-CA / CG-CN (0.10) 1.56 times, 1.15 times and 1.52 times of that. Fig.10 (c) is the degradation curve of TC. With the increase of CG-CN dosage, the degradation efficiency first increases and then decreases. (0.10) It still showed the best photocatalytic activity, with a reaction rate of 0.0455min -1 , respectively EE-CA / CGCN (0.05) EE-CA / CGCN (0.15) and E-CA / CGCN (0.10) 1.51, 1.26 and 1.81 times ( Fig.10 (d)). The excellent photocatalytic activity of this composite material is mainly due to the fact that CG-CN is anchored on the fiber by electrospraying, exposing more active sites, thereby improving the catalytic activity of the material.

[0121] like Fig.10 As shown in (e), EE-CA / CGCN (0.10)Degradation performance of fiber membrane for different dyes. When MB is the target pollutant, the degradation rate at 30 min is 98.54%, which is higher than that of RhB (56.58%) and MO (43.13%). The reaction rate is 0.1341 min -1 , which are 6.35 and 8.13 times of those of RhB and MO, respectively. (0.10) The fiber membranes all showed their photocatalytic degradation performance, but the photocatalytic activities they showed were different.

[0122] From the application point of view, stability and reusability are important criteria for evaluating catalysts. Fig.11 It can be seen that EE-CA / CGCN (0.10) The degradation rates of MB dye by the fiber membrane in five consecutive cycles of photocatalytic degradation tests were 99.31%, 98.85%, 98.09%, 97.01% and 96.08%, respectively. The gradual decrease in the degradation rate may be due to the EE-CA / CGCN (0.10) However, the degradation rate of EE-CA / CGCN was still more than 96% in the fifth cycle test, which indicated that (0.10) It not only has good reusability but also exhibits excellent photocatalytic stability.

[0123] (4) Three-dimensional fluorescence spectroscopy

[0124] Further study of EE-CA / CGCN using three-dimensional fluorescence spectroscopy (0.10) The photocatalytic degradation process of different organic dyes by fiber membranes. Fig.12 (ac) are shown. Before the photocatalytic reaction, MB has two three-dimensional fingerprint peaks at 500-700nm and 250-300nm. After the adsorption-desorption equilibrium is reached in the dark reaction for 30 minutes, the intensity of the two three-dimensional fingerprint peaks weakens. As the photocatalytic reaction proceeds, the color of the MB solution gradually fades. After 30 minutes of illumination, the three-dimensional fingerprint peak almost completely disappears, and the MB solution is almost colorless. This shows that the strong chromogenic groups in the MB molecule are affected by the photocatalytic degradation reaction of g-C3N4, and the large conjugated system is destroyed. However, as Fig.12 As shown in (di), when RhB and MO organic dyes were used for simulated pollution, the spectral signals and colors of RhB and MO dyes only changed slightly. Therefore, the changes in the three-dimensional fingerprint peaks before and after degradation indicate that EE-CA / CGCN (0.10) The fiber membrane had weak degradation performance for RhB and MO dyes within 30 min, but had good photocatalytic degradation efficiency for MB dye.

[0125] (5) Photocatalytic mechanism

[0126] In order to compare the contribution of different free radicals to the oxidative degradation of MB, four different quenchers were selected for quenching tests. Generally speaking, p-benzoquinone (BQ) can be used as a ·O2 - The quencher, triethanolamine (TEOA) can effectively quench h + , isopropyl alcohol (IPA) can remove ·OH. Fig.13 (a) shows the EE-CA / CGCN (0.10) The quenching test results of the fiber membrane showed that after adding BQ quencher, the degradation efficiency of MB dropped from 97.62% to 51.70%, which indicated that the O2 - It plays a certain role in the oxidative degradation of MB, while the inhibitory effect of IPA is basically negligible, which shows that ·OH has a slight inhibitory effect on the system. In addition, the addition of TEOA leads to a 52.82% decrease in the degradation rate of MB, showing the strongest inhibitory effect, proving that h + It may be one of the main active species in this system. - 、h + and OH both participated in EE-CA / CGCN (0.10) The oxidative degradation process of MB by fiber membrane, where h + and O2 - It is the main contributor to active free radicals.

[0127] (6) Photocatalytic antibacterial

[0128] In order to accurately evaluate EE-CA / CGCN (0.05) The antibacterial properties of the fiber membrane were studied. The antibacterial tests without membrane catalyst and membrane catalyst under dark conditions were used as blank control groups. The other group used membrane catalyst for photocatalytic antibacterial test under visible light (λ>420nm). Finally, the bacterial colony counts of the three groups were calculated. The results are as follows: Fig.14 (al) As shown. It can be observed that Fig.14 (ad) In the blank test under visible light (λ>420nm), the colony count after illumination changed little, indicating that visible light with λ>420nm has a weak killing effect on E. coli. (0.10) The fiber membrane was tested for antibacterial properties under light-proof conditions to observe the antibacterial activity of EE-CA / CGCN. (0.10) Does the fiber membrane itself have antibacterial properties? Fig.14 As shown in (eh), after 60 min, the number of E. coli colonies did not change much. Therefore, EE-CA / P25 was excluded. (0.10) The fiber membrane may be antibacterial under lightless conditions. Therefore, under visible light (λ>420nm), the EE-CA / CGCN (0.10)The fiber membrane was tested for photocatalytic antibacterial effects. Fig.14 As shown in (il), it can be found that the number of E. coli colonies gradually decreases with the extension of illumination time. After 60 minutes of illumination, there are only a few colonies on the culture medium, which proves that EE-CA / CGCN (0.10) The fiber membrane has the ability of photocatalytic sterilization. The corresponding bacterial survival rate and antibacterial efficiency are shown in Fig.14 In (mn), it can be seen that the bacterial survival rate in the blank control group and under light-proof conditions is above 90%. (0.10) The removal rate of E. coli by the fiber membrane is as high as 90.12%, and the bacterial survival rate is only 9.88%. (0.10) The fiber membrane has good antibacterial properties under light. In summary:

[0129] In summary:

[0130] The bulk g-C3N4(CN) was synthesized by high-temperature pyrolysis, and then the powdered CG-CN catalyst was obtained by freeze grinding. The powdered CG-CN catalyst was loaded onto nanofibers by electrospinning-electrospray (EE) to prepare EE-CA / CGCN fiber membrane. Compared with the traditional electrospinning method, the g-C3N4 particles of the EE-CA / CGCN fiber membrane were more exposed on the surface of the nanofibers, providing more active sites, which was beneficial to improve the photocatalytic performance. The CG-CN of the EE-CA / CGCN fiber membrane was evenly dispersed on the fiber surface, which inhibited the agglomeration of nanoparticles to a certain extent and improved the stability of the membrane catalytic material.

[0131] When the loading amount of CG-CN is 0.10 g, EE-CA / CGCN (0.10) It showed better adsorption and photocatalytic performance, with the degradation rate of MB reaching 98.54% after 30 minutes of illumination, and the degradation rate of TC reaching 94.34% after 60 minutes of illumination. (0.10) It showed good antibacterial performance against Escherichia coli, with an antibacterial rate of 90.12%. (0.10) Fiber membrane is a highly efficient catalyst for pollutant degradation and antibacterial properties, which is of great significance for reducing environmental pollution and promoting sustainability.

[0132] The above are only preferred embodiments of the present invention and the technical principles used. Those skilled in the art will understand that the present invention is not limited to the specific embodiments described herein, and that various obvious changes, readjustments and substitutions can be made by those skilled in the art without departing from the scope of protection of the present invention. Therefore, although the present invention is described in more detail through the above embodiments, the present invention is not limited to the above embodiments, and may include more other equivalent embodiments without departing from the concept of the present invention, and the scope of the present invention is determined by the scope of the appended claims.

Claims

1. A method for preparing a rice straw-derived cellulose acetate / g-C3N4 fiber membrane, characterized in that: The following steps are involved: Mixing dichloromethane and acetic acid uniformly to obtain a mixed solvent, adding rice straw-derived cellulose acetate and polyvinyl pyrrolidone powder into the mixed solvent and stirring to obtain a CA / PVP spinning solution; The urea is heated in a muffle furnace to prepare g-C3N4 nanosheets, and the g-C3N4 nanosheets are placed in a cryogenic grinding machine, and the cryogenic grinding parameters are adjusted to grind the g-C3N4 nanoparticles; The g-C3N4 nanoparticle powder is mixed with an anhydrous ethanol solution, subjected to ultrasonic treatment, and subjected to magnetic stirring to obtain a g-C3N4 electrospray solution; EE-CA / PVP / g-C3N4 fiber membrane was prepared by electrospinning-electrospray technology, using CA / PVP spinning solution and g-C3N4 electrospray solution for simultaneous electrospinning and electrospinning, respectively, to evenly anchor g-C3N4 nanoparticles on the fiber surface to obtain EE-CA / PVP / g-C3N4 fiber membrane; The EE-CA / PVP / g-C3N4 fiber membrane was immersed in deionized water to remove polyvinyl pyrrolidone, and then freeze-dried to obtain a rice straw-derived cellulose acetate / g-C3N4 fiber membrane.

2. The method for preparing the rice straw-derived cellulose acetate / g-C3N4 fiber membrane according to claim 1, characterized in that: The mass ratio of the rice straw-derived cellulose acetate to the polyvinyl pyrrolidone powder is (3-5):1; the volume ratio of the dichloromethane to the acetic acid is (1-3):1, and the concentration of the polyvinyl pyrrolidone powder in the mixed solvent is 0.025-0.05 g / mL.

3. The method for preparing the rice straw-derived cellulose acetate / g-C3N4 fiber membrane according to claim 2, characterized in that: The concentration of the g-C3N4 nanoparticle powder relative to the mixed solvent is 0.01 to 0.025 g / mL; in the g-C3N4 electrospray solution, the concentration of the g-C3N4 nanoparticle powder relative to the anhydrous ethanol is 0.003 to 0.01 g / mL.

4. The method for preparing the rice straw-derived cellulose acetate / g-C3N4 fiber membrane according to claim 1, characterized in that: During the heating reaction in the muffle furnace, the temperature is raised to 500-550° C. at a rate of 3-6° C. / min and kept warm for 4-6 hours; the freezing grinding parameters include: a grinding time of 30-90 seconds and a grinding frequency of 25-35 Hz.

5. The method for preparing the rice straw-derived cellulose acetate / g-C3N4 fiber membrane according to claim 1, characterized in that: The electrospinning-electrospraying technology device comprises an electrospinning machine, an electrostatic sprayer and a rotary drum collecting device, wherein the electrospinning machine is placed on one side of the rotary drum collecting device, and the electrostatic sprayer is placed on the other side of the rotary drum collecting device; When the electrospinning-electrospraying technology is used, an electrospinning machine and an electrostatic sprayer are used simultaneously to perform electrospinning and electrostatic spraying respectively, and a rotary drum collection device is used for collection. The electrostatic sprayer is not connected to a high-voltage power supply when in use. The electrospinning-electrospraying technology allows the nanoparticles in the electrospray liquid to be evenly dispersed on the fiber surface.

6. The method for preparing the rice straw-derived cellulose acetate / g-C3N4 fiber membrane according to claim 5, characterized in that: The electrospinning process parameters include: spinning temperature of 23-27°C, humidity of 45-55%, spinning positive voltage of 8-12kV, spinning negative voltage of -4--6kV, feeding speed of 0.3-0.5ul / min, and the distance between the spinneret and the drum collecting device of 10-20cm.

7. The method for preparing the rice straw-derived cellulose acetate / g-C3N4 fiber membrane according to claim 1, characterized in that: The preparation method of the rice straw-derived cellulose acetate comprises: The rice straw is washed, dried, crushed and sieved to obtain rice straw powder, the rice straw powder is pretreated with an ethanol solution in a high temperature reactor, and then subjected to an alkali treatment and H2O2 bleaching to obtain rice straw-derived cellulose; Acetic anhydride and glacial acetic acid are added to the rice straw-derived cellulose to prepare rice straw-derived cellulose acetate through acetylation reaction.

8. The method for preparing the rice straw-derived cellulose acetate / g-C3N4 fiber membrane according to claim 7, characterized in that: The rice straw particle size is 50 to 100 meshes; During the pretreatment process, the mass concentration of the ethanol solution is 60-70wt%, the heating reaction temperature is 160-240°C, and the reaction time is 2-3h; During the alkali treatment and H2O2 bleaching process, 4-6 wt% alkali solution is used to stir and react at 85-95°C for 1.5-2.5 hours, and after the reaction is completed, it is filtered, and then heated and stirred with 2 wt% H2O2 solution at 65-75°C for 1.5-2.5 hours to obtain rice straw-derived cellulose; During the acetylation reaction, the mass ratio of the rice straw-derived cellulose to the acetic anhydride is 1:(3-5), and the concentration range of the rice straw-derived cellulose in the glacial acetic acid is 0.05-0.07 g / mL.

9. A rice straw derived cellulose acetate / g-C3N4 fiber membrane, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8.

10. An application of the rice straw derived cellulose acetate / g-C3N4 fiber membrane according to claim 9, characterized in that: The rice straw-derived cellulose acetate / g-C3N4 fiber membrane is used as a photocatalyst in water pollution treatment and photocatalytic sterilization.

Citation Information

Patent Citations

  • Degradable spinning raw material, degradable fiber membrane and degradable protective cover

    CN111286175A

  • Carbon nitride / lanthanum hydroxide nanofiber membrane as well as preparation method and application thereof

    CN112076785A

  • Method for preparing cellulose acetate and P25 porous flexible fiber membrane through electrospinning, obtained porous flexible fiber membrane and application of porous flexible fiber membrane

    CN112430910A

  • Composite membrane as well as preparation method and application thereof

    CN114405284A

  • Inorganic particle composite fiber sponge dressing and preparation and application thereof

    CN118542962A